Molecular epidemiology and phylogenomic analysis of Mycobacterium abscessus clinical isolates in an Asian population. Issue 11 (30th November 2021) - Chew, Ka Lip; Octavia, Sophie; Jureen, Roland; Ng, Oon Tek; Marimuthu, Kalisvar; Lin, Raymond Tzer Pin; Teo, Jeanette W. P.
Abstract : Mycobacterium abscessus comprises three subspecies : M. abscessus subsp. abscessus, M. abscessus subsp. bolletii, and M. abscessus subsp. massiliense . These closely related strains are typically multi-drug-resistant and can cause difficult-to-treat infections. Dominant clusters of isolates with increased pathogenic potential have been demonstrated in pulmonary infections in the global cystic fibrosis (CF) population. An investigation was performed on isolates cultured from an Asian, predominantly non-CF population to explore the phylogenomic relationships within our population and compare it to global M. abscessus isolates. Whole-genome-sequencing was performed on M. abscessus isolates between 2017 and 2019. Bioinformatic analysis was performed to determine multi-locus-sequence-type, to establish the phylogenetic relationships between isolates, and to identify virulence and resistance determinants in these isolates. A total of 210 isolates were included, of which 68.5 % (144/210) were respiratory samples. These isolates consisted of 140 (66.6 %) M . abscessus subsp. massiliense, 67 (31.9 %) M . abscessus subsp. abscessus, and three (1.4 %) M . abscessus subsp. bolletii . Dominant sequence-types in our population were similar to those of global CF isolates, but SNP differences in our population were comparatively wider despite the isolates being from the same geographical region. ESX (ESAT-6 secretory) cluster three appeared to occur most commonly in ST4 and ST6 M. abscessus subsp. massiliense, but other virulence factors did not demonstrate an association with isolate subspecies or sample source. We demonstrate that although similar predominant sequence-types are seen in our patient population, cross-transmission is absent. The risk of patient-to-patient transmission appears to be largely limited to the vulnerable CF population, indicating infection from environmental sources remains more common than human-to-human transmission. Resistance and virulence factors are largely consistent across the subspecies with the exception of clarithromycin susceptibility and ESX-3.